RETHINKING CORPORATE PRIORITIES: THE SURGE OF ESG INVESTING AND GREENWASHING RISKS - Aik, Nai Chiek (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
ESG investing, centered on a company's environmental, social, and governance practices, has surged in popularity as businesses recognize the imperative of catering to a wider array of stakeholders beyond shareholders. Investors have transitioned from a profit-centric ethos to one that prioritizes broader societal impact. Evaluation criteria now encompass a company's commitment to ESG principles and responsible business conduct. This transformative investor perspective encourages companies to openly embrace ESG integration, particularly emphasizing environmental considerations. Nevertheless, the specter of greenwashing, where companies engage in deceptive practices to feign environmental responsibility, persists as a contentious issue in the ongoing dialogue surrounding ESG investing.